Study on physical clogging process and practical application of horizontal subsurface flow constructed wetland - Shuqun Dai; Ruida Wang; Jiawei Lin; Guoyi Zhang; Zhonggou Chen; Lei Li; Qintian Shi (Scientific Reports)
Abstract In view of the urgent concerns pertaining to the proliferation of rural wastewater discharges and the imperative for decentralized treatment, this article examines the phenomenon of physical clogging in a small-scale horizontal submerged flow artificial wetland system. Through a combination of experimental analysis and CFD-EDM numerical simulations, the impact of clogging on the hydraulic efficiency of the system was subjected to rigorous examination. Based on these findings, an innovative design strategy was proposed, namely the addition of vertical baffles. The experimental results demonstrate that this strategy can markedly prolong the duration of complete clogging of the system by up to 15% and enhance the hydraulic efficiency by 21%. Based on this, a small-scale horizontal submerged artificial wetland wastewater treatment system was designed for rural areas and successfully implemented in Fanrong Village, Rui’an City. This resulted in an enhanced wastewater treatment effect and an improved rural landscape. The findings of this study contribute to the development of a more rational and effective sewage treatment solution for rural areas.